The principle of preventing the threat of force in international relationsWithin the framework of the Charter of the United Nations - HUSIN, AMIR; ALMARZOOQI, YOUSIF ABDULLA; HASSAN, FAREED BIN MOHD; WARDI, FITHRIAH (Journal of Economic, Administrative and Legal Sciences, 2019)
The study dealt with the principle of preventing the threat of use of force in international relations within the framework of the Charter of the United Nations by stating the content of the principle of preventing the threat of use of force in accordance with Article 2/4 of the Charter of the United Nations and analyzing legitimate exceptions to the use of force in accordance with the provisions of general international law. In order to achieve the objectives of the research, the descriptive approach was adopted to analyze the provisions of the Charter of the United Nations and international law and the international conventions governing the principle of preventing the threat of force in international relations and the views of scholars of international law. The problem of research is highlighted in the weaknesses of the Charter of the United Nations Force in international relations. The study concluded that the principle of preventing the threat of force in international relations was one of the fundamental pillars of the international legal order established by the Charter of the United Nations. The study reached a number of recommendations, the most important being the re-evaluation of measures to maintain international peace and security through a review of The Security Council acted by reducing the veto.